2017
DOI: 10.1038/s41598-017-17265-6
|View full text |Cite
|
Sign up to set email alerts
|

The positivity of estrogen receptor and progesterone receptor may not be associated with metastasis and recurrence in epithelial ovarian cancer

Abstract: The estrogen (ER) or progesterone receptors (PR) is positively associated with better clinical outcomes in ovarian cancer. Whether metastasis or recurrence of ovarian cancer is correlated with this association has not been investigated. Data on 894 women with epithelial ovarian cancer were collected and the association between ER or PR positivity and peritoneal or lymph node metastases or recurrence was analysed. ER or PR positivity was higher in high-grade, low-grade serous and endometrioid carcinoma, but low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In their study of sex steroid hormone receptors expressed in ovarian carcinomas, Gomora MJ 12 . However, other studies confirmed ER positivity in these tumors, associated with recurrent disease and peritoneal metastasis 13 . Also, other studies stated that LG tumors have higher ER and PR expression compared to HG tumors and that estrogen receptor expression was associated with increased risk of lympho-vascular space invasion 14,15 .…”
Section: Resultsmentioning
confidence: 82%
“…In their study of sex steroid hormone receptors expressed in ovarian carcinomas, Gomora MJ 12 . However, other studies confirmed ER positivity in these tumors, associated with recurrent disease and peritoneal metastasis 13 . Also, other studies stated that LG tumors have higher ER and PR expression compared to HG tumors and that estrogen receptor expression was associated with increased risk of lympho-vascular space invasion 14,15 .…”
Section: Resultsmentioning
confidence: 82%
“…The difference in the incidence of endometrial and ovarian cancers may result in differences in clinical characteristics and pathological parameters by ethnicities. Our previous studies reported that endometrial and ovarian cancers occur more frequently in Chinese women before menopause [22][23][24], whilst 75% of endometrial and ovarian cancers occur after menopause in Caucasians [25]. Our recent unpublished data also showed differences in clinical characteristics and pathological parameters in breast cancer between Chinese and New Zealand Europeans.…”
Section: Ivyspringmentioning
confidence: 68%
“…GPR30 expression is higher in EAOC than in benign OE (96). The upregulation of ESR expression is associated with a better clinical outcome in ovarian cancer (95) and CCC (14), suggesting the role of ESR in tumor initiation or the early development of primary EC, but not in EC progression.…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 96%
“…There are two types of estrogen receptors (ESRs), ESR1 (also known as ERα) and ESR2 (ERβ). The ESR expression level has been shown to be higher in EC and high-grade serous than in CCC and mucinous carcinoma (95). Among EAOC, ESR positivity has been shown to be significantly higher in EC (91%), but lower in CCC (8%) (60).…”
Section: Similar Epigenetic Modifications: Gene-environment Interactimentioning
confidence: 99%
See 1 more Smart Citation